The FAST Workstation Shows Construct Validity and Participant Endorsement - Baxter, Jonathan A.; Bhamber, Nivraj S.; Patel, Rakesh S.; Tennent, Duncan (Arthroscopy, Sports Medicine, and Rehabilitation, 2021)
To determine in what way the proposed simulation-based intervention (SBI) is an effective intervention for use in basic arthroscopic skills training. Twenty candidates were recruited and grouped according to experience. Performance metrics included the time to activity completion, errors made, and Global Rating Scale score. Qualitative data were collected using a structured questionnaire. Performance on the SBI differed depending on previous arthroscopic training received. Performance on the simulator differed between groups to a statistically significant level regarding time to completion. A difference was also present between participants with no previous training and those with previous training when assessed using the Global Rating Scale. The SBI was deemed acceptable, user-friendly, and realistic. Participants practicing at the expert level believe that such an SBI would be beneficial in developing basic arthroscopic skills. The results of this study provide evidence that the use of an SBI consisting of a benchtop workstation, laptop viewing platform, 30° arthroscope, and defined performance metrics can detect differences in the level of arthroscopic experience. This format of SBI has been deemed acceptable and useful to the intended user, increasing the feasibility of introducing it into surgical training. This study adds to the existing body of evidence supporting the potential benefits of benchtop SBIs in arthroscopic skills training. Improved performance on such an SBI may be beneficial for the purpose of basic arthroscopic skills training, and we would support the inclusion of this system in surgical training programs such as those developed by the Arthroscopy Association of North America and American Board of Orthopaedic Surgery.